In vivo antimalarial effect of 1-hydroxy-5,6,7-trimethoxyxanthone isolated from Mammea siamensis T. Anders. flowers: pharmacokinetic and acute toxicity studies - Prapaporn Chaniad; Arnon Chukaew; Prasit Na-ek; Gorawit Yusakul; Litavadee Chuaboon; Arisara Phuwajaroanpong; Walaiporn Plirat; Atthaphon Konyanee; Abdi Wira Septama; Chuchard Punsawad (BMC, 2024)
Abstract Background The potent antiplasmodial activity of 1-hydroxy-5,6,7-trimethoxyxanthone (HTX), isolated from Mammea siamensis T. Anders. flowers, has previously been demonstrated in vitro. However, its in vivo activity has not been reported. Therefore, this study aimed to investigate the antimalarial activity and acute toxicity of HTX in a mouse model and to evaluate the pharmacokinetic profile of HTX following a single intraperitoneal administration. Methods The in vivo antimalarial activity of HTX was evaluated using a 4-day suppressive test. Mice were intraperitoneally injected with Plasmodium berghei ANKA strain and given HTX daily for 4 days. To detect acute toxicity, mice received a single dose of HTX and were observed for 14 days. Additionally, the biochemical parameters of the liver and kidney functions as well as the histopathology of liver and kidney tissues were examined. HTX pharmacokinetics after intraperitoneal administration was also investigated in a mouse model. Liquid chromatography triple quadrupole mass spectrometry was used to quantify plasma HTX and calculate pharmacokinetic parameters with the PKSolver software. Results HTX at 10 mg/kg body weight significantly suppressed parasitemia in malaria-infected mice by 74.26%. Mice treated with 3 mg/kg HTX showed 46.88% suppression, whereas mice treated with 1 mg/kg displayed 34.56% suppression. Additionally, no symptoms of acute toxicity were observed in the HTX-treated groups. There were no significant alterations in the biochemical parameters of the liver and kidney functions and no histological changes in liver or kidney tissues. Following intraperitoneal HTX administration, the pharmacokinetic profile exhibited a maximum concentration (Cmax) of 94.02 ng/mL, time to attain Cmax (Tmax) of 0.5 h, mean resident time of 14.80 h, and elimination half-life of 13.88 h. Conclusions HTX has in vivo antimalarial properties against P. berghei infection. Acute toxicity studies of HTX did not show behavioral changes or mortality. The median lethal dose was greater than 50 mg/kg body weight. Pharmacokinetic studies showed that HTX has a long elimination half-life; hence, shortening the duration of malaria treatment may be required to minimize toxicity.